Nature and Animal World: The Dominant Themes in Ted Hughes's Poetry: Exploring the Dominant Themes of Nature and Animals in Ted Hughes's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nature and animal world are the dominant themes in Ted Hughes's poetry, since nature manifests the elemental energy and the animals inherit those instinctive characteristics which impart them the power to accommodate with this. Hughes conceives that the whole of the universe is directed and regulated by the bigger energy that pervades like power circuit through it, he calls it - elemental power circuit (TCP, 103). He is convinced that it is the energy, very much real, that manifests in the various appearances of nature, and is, in itself the driving force to its manifestation. The universe is a complex web, where element, animal and human being exist with their characteristics yet form a complex - a unified whole, Hughes's vision of 'energy-circuit parallels with the Indian concept of Shakti, which recognizes 'Shakti' as the deity of energy and power and is reckoned as the root cause of creation as well as destruction of the universe. The Shakti is the essence of every element that sets it to life.